2018
DOI: 10.2147/ott.s171724
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of bevacizumab-based combination therapy for treatment of patients with metastatic colorectal cancer

Abstract: AimThe use of bevacizumab in combination therapy is an emerging trend in metastatic colorectal cancer treatment. However, the clinical value of different combination types remains under debate. Thus, a meta-analysis of randomized controlled trials (RCTs) comparing bevacizumab-based combination therapy with monotherapy (therapy that uses one type of treatment, such as chemotherapy or surgery alone, to treat metastatic colorectal cancer) was performed, aiming to evaluate the safety and efficacy of bevacizumab-ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…Most of the ongoing trials are currently focused on assessing the combination of anti-VEGF therapy with chemotherapeutic agents (215) or immunotherapies (216,217). A meta-analysis of randomized control trials comparing the effect of different chemotherapeutic drugs alone, or in combination with bevacizumab, in metastatic colorectal cancer showed a beneficial effect of the combination in extending OS, PFS, and ORR (218). However, many other trials have reported no clinical benefit in adding the anti-VEGF antibody to their combinations.…”
Section: Tumor Vasculaturementioning
confidence: 99%
“…Most of the ongoing trials are currently focused on assessing the combination of anti-VEGF therapy with chemotherapeutic agents (215) or immunotherapies (216,217). A meta-analysis of randomized control trials comparing the effect of different chemotherapeutic drugs alone, or in combination with bevacizumab, in metastatic colorectal cancer showed a beneficial effect of the combination in extending OS, PFS, and ORR (218). However, many other trials have reported no clinical benefit in adding the anti-VEGF antibody to their combinations.…”
Section: Tumor Vasculaturementioning
confidence: 99%
“…Previous publications described no increase in survival using these agents after resectable or unresectable disease[64,66]. Conversely, a recent meta-analysis[67] on the different types of anti-VEGF antibody combination therapies has shown a significant improvement in progression-free survival, overall survival and response rate.…”
Section: The Role Of Systemic Chemotherapymentioning
confidence: 99%
“…According to a very recent systematic review and meta-analysis the addition of anti-VEGFR2 targeting agents to the first- or second-line chemotherapy could prolong patient's OS and PFS in advanced or metastatic gastric cancer (16). The study also highlighted the inefficacy of anti-VEGFA therapy in this type of tumor, unlike what observed in other type of cancers (5356). Thus, to better characterize the quality of the gastric cancer-associated vasculature by pCLE may grant the possibility to predict which patients will be more likely to respond to anti-angiogenic therapy, sparing the others from costly ineffective treatments and side effects.…”
Section: Discussionmentioning
confidence: 61%